ETR 300 : Terrariums And Souvenirs / Khairul Farhi Yusob ... [et al.] - Yusob, Khairul Farhi; Yusof, Mohammad Shamsul; Mohamed Nor, Yasser Alsidek (2000)
S.E is a company which selling and distributing home decor (terrariums) and souvenirs. For any further information, S.E will explain what is meant by terrariums. Terrariums are wonderful, magical environments. Decorative, attractive, and easy to care for, just plant and forget. Because terrariums recycle their moisture, they need very little attention. A closed terrarium can often go a month or more between watering. They actually thrive on neglect! Now even people who tend to neglect plants can develop a "Green Thumb".